Case of Bistieva and Others v. Poland - Kosińska, Anna Magdalena (Polish Review of International and European Law, 2020)
The present commentary concerns the claims alleging a violation under Article 5 paragraph 1 (the right to liberty and security of a person) and paragraph 4 (the right to take proceedings to determine the lawfulness of the detention) of the European Convention on Human Rights and Article 8 (the right to respect for private and family life) ECHR by using detention by the Republic of Poland for the period of almost 6 months with regard to a family of third-country nationals. The applicant in the case was a national of Russia, Zita Bistieva and her three minor children. The judgement under discussion is significant from the perspective of strengthening the guarantees for the protection of the rights of irregular migrants in the system of both the Council of Europe and the European Union, on the grounds of the concept of equivalent protection adopted in EU primary law. The ruling in question also refers to the fact that the Member States do not sufficiently resort to alternative measures with regard to the detention of foreign nationals.